Terry Pratchett's Narrative Worlds From Giant Turtles to Small Gods (Critical Approaches to Children's Literature, 2018)
This book highlights the multi-dimensionality of the work of British fantasy writer and Discworld creator Terry Pratchett. Taking into account content, political commentary, and literary technique, it explores the impact of Pratchett's work on fantasy writing and genre conventions. With chapters on gender, multiculturalism, secularism, education, and relativism, Section One focuses on different characters' situatedness within Pratchett's novels and what this may tell us about the direction of his social, religious and political criticism. Section Two discusses the aesthetic form that this criticism takes, and analyses the post- and meta-modern aspects of Pratchett's writing, his use of humour, and genre adaptations and deconstructions. This is the ideal collection for any literary and cultural studies scholar, researcher or student interested in fantasy and popular culture in general, and in Terry Pratchett in particular. Marion Rana is a post-doctoral researcher at the University of Bremen, Germany, where she is in charge of a project analysing the negotiation of deafness in children's literature. She is one of the publishers of interjuli, an international journal for research in children's literature. Her recent publications deal with disability poetry, the commodification of sexuality in dystopian fiction, as well as categories of simplicity and the use of Young Adult literature in the foreign language classroom.